2019
DOI: 10.1177/2164956119856856
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Psychological and Occupational Well-being Following a Brief Yoga-Based Program for Education Professionals

Abstract: Objective The purpose of this study was to examine changes in psychological and occupational well-being in education professionals who attended a yoga-based program. Methods Education professionals who attended a 3-day yoga-based RISE (resilience, integration, self-awareness, engagement) program were recruited to participate. RISE was administered at the Kripalu Center for Yoga & Health. Measures of psychological and occupational well-being, and health-related behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
(66 reference statements)
1
6
0
1
Order By: Relevance
“…For researchers interested in individuals exposed to stress and trauma, contextual understanding of increases in wellness outcomes (Trent et al, 2018 ) can provide meaningful tools for interventions and suggestions for assessment. For individuals in professions exposed to high amounts of stress and/or trauma, the current findings in conjunction with previous RISE reports (Dyer et al, 2020 ; Trent et al, 2018 , 2019a ) give support for the construction of positive experiences and evidence for mechanisms influencing outcomes in a yoga-based retreat setting.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…For researchers interested in individuals exposed to stress and trauma, contextual understanding of increases in wellness outcomes (Trent et al, 2018 ) can provide meaningful tools for interventions and suggestions for assessment. For individuals in professions exposed to high amounts of stress and/or trauma, the current findings in conjunction with previous RISE reports (Dyer et al, 2020 ; Trent et al, 2018 , 2019a ) give support for the construction of positive experiences and evidence for mechanisms influencing outcomes in a yoga-based retreat setting.…”
Section: Discussionsupporting
confidence: 83%
“…Yoga decreases anxiety in depression with clinical populations (Kwok et al, 2019 ). Over several years, Kripalu Yoga programmes have demonstrably improved psychological and physical health indicators in many populations, including youth in schools (Butzer et al, 2017 ), police officers (Jeter et al, 2013 ), obese populations (Braun et al, 2012 ), mental health professionals (Riley et al, 2017 ), educators (Trent et al, 2019a ), physicians (Scheid et al, 2020 ), and heterogeneous groups of frontline professionals (Dyer et al, 2020 ; Trent et al, 2018 , 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, students are required to maintain a gentle and introspective attitude throughout the practice. Each pose of Kripalu Yoga needs to be maintained for a long time in order to fully release the pent-up emotions[ 96 ]. Kripalu Yoga has achieved significant intervention effects in one study, which may be related to its emphasis on obeying the wisdom of the body[ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown after a brief intervention, participants show improvements in perceived stress, mindfulness, empowerment, positive affect, negative affect, selfcompassion, total work engagement, vigor, sleep quality, resilience, satisfaction with life, as well as reduced professional burnout (all P values < .01). 50 As a contemplative activity incorporating attention training, breath awareness, and integration of breath and movement, yoga explores and strengthens the connection between the body, mind, and spirit. Evidence shows regular yoga practice leads to improvement in the cardiopulmonary risk profile, 51 anti-inflammatory effects, 52 relief of pain, 53 and attentional control, 54 as well as enhancement of executive functioning and working memory, buffering age-related decline.…”
Section: Composition Of Behavior Change Interventionsmentioning
confidence: 99%